Development of Online Store Marketing Strategy for Obsolete Fashion Shukufukuu.Id - Zatalini, Halimah; Achsani, Noer Azam; Retnaningsih (School of Business, IPB University (SB-IPB), 2024)
Obsolete fashion is a potential market in Indonesia. The increasing trend of public consumption is utilized by Shukufukuu.Id to sell used fashion clothes. However, Shukufukuu.Id's revenue has stagnated. This research is designed to create alternative marketing strategies as a solution to the problem. The method of determining respondents in this study uses non-probability sampling with a convenience sampling technique. Research respondents were taken from potential consumer respondents totaling 33 people and Shukufukuu.Id respondents totaling 30 people. The analytical tool used in this research is the product elements (product), price, promotion, distribution channels (place), personalization, privacy, customer service, community, security, site, and sales promotion (4P+P2C2S3) marketing mix. The data in this study were analyzed using descriptive analysis and importance-performance analysis (IPA). The results showed that there are five variables with high expectations but have not met customer satisfaction, namely the diversity of clothing types, unique clothing models, clothing designs, free shipping promos on first purchases, and promos at the end of the month. Based on IPA calculations and the owner's view of the problems faced and solutions, alternative marketing strategies are designed in the form of increasing the variety of clothes sold, sales promotions that can increase customer satisfaction and brand awareness, and sales promotions that can change consumer behavior. Keywords: marketing mix 4P+P2C2S3, importance performance analysis, obsolete fashion, alternative marketing strategies, fashion trend